2016
DOI: 10.1055/s-0036-1582427
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Bone Grafts from the Dorsal Wrist for the Treatment of Kienböck Disease

Abstract: Previous literatures described various methods of treatment for Kienböck disease depending on the patient characteristics, the severity of the symptom, and radiological staging. 1-8 Treatment options range from conservative measurements to surgical interventions. 9-12 Several authors advocated a biomechanical approach to reduce load transmission on the necrotic lunate, [13][14][15][16][17][18][19] and good clinical results have been reported in joint leveling procedures such as radial shortening or ulnar lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Four articles approximately 4+5 ECA for Kienböck's disease (stages II, III) and one article for scaphoid nonunion met inclusion criteria and were included in the study. 5,[36][37][38] In total there were 54 patients with Kienböck's disease. The mean follow-up in these studies was 45 months (20-70 months).…”
Section: +5 Extracompartmental Artery Bone Graftmentioning
confidence: 99%
“…Four articles approximately 4+5 ECA for Kienböck's disease (stages II, III) and one article for scaphoid nonunion met inclusion criteria and were included in the study. 5,[36][37][38] In total there were 54 patients with Kienböck's disease. The mean follow-up in these studies was 45 months (20-70 months).…”
Section: +5 Extracompartmental Artery Bone Graftmentioning
confidence: 99%
“…The current techniques for regenerating vascular flow, termed vascularized bone grafting methods, are the mainstream therapies for advanced Kienböck disease. [2,3] Multiple short-term [4] or mid-term [5] clinical trials have reported the usefulness of vascularized bone grafting in patients with advanced Kienböck disease; meanwhile, few long-term clinical results are available, [6] with follow-up no longer than 15 years. Since the first report of Saffar [7] on Kienböck disease treatment with vascularized os pisiform transferring (VOPT), the procedure has become a useful approach for treating Kienböck disease affecting the wrist, due to its ability to relieve pain, improve grip strength, and enhance the range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that compromised vascularization of the lunate is the most important pathogenetic factor in Kienbo ¨ck's disease. This is addressed by techniques using local or free vascularized corticocancellous bone grafts (Arora et al, 2008, Daecke et al, 2005a, 2005bMatsumoto et al, 2018;Moran et al, 2005;Nakagawa et al, 2016;Tsantes et al, 2019;von Maydell and Bru ¨ser, 2008;Ye et al, 2020). Vascularized bone grafts alone do not allow reconstruction of a joint surface, especially the radiolunate cartilage.…”
Section: Discussionmentioning
confidence: 99%